Analysis of the Influence of Communication on Employee Performance Satisfaction with Supervision as a Mediating Variable at Private Contractor Company - Jinqiang, Shi (International Journal of Scientific Research and Management (IJSRM), 2021)
Private project worker organization in Medan declined as of late. Decrease in Representative Fulfillment is brought about by a few things; diminished nature of correspondence and management. The examination tests were drawn by utilizing the immersion recipe comprising of 70 representatives. The halfway testing showed that correspondence has a positive and huge impact on representative fulfillment, wherein the T-count is 4.392 and the worth of T-table is 1.66691, then, at that point, the worth of T-count> T-table (4.392> 1.66691) with huge worth of 0,000> 0.05. The incomplete testing showed that management has a positive and huge impact on worker work fulfillment, in which the worth of oversight variable T-count 2.015> T-table 1.66691 with an importance worth of 0.005> 0.05. All the while, correspondence and management have a positive and critical impact on worker work fulfillment up to 15,467 in which F-table is 2.74.